Indoor air quality monitoring system control: article / Daisy Ubong Lawai - Ubong Lawai, Daisy (2011)
In this project report, sensitivity detection of various smells in the room is discussed by using air sensor MQ-2. People do not perform well on their job when they are uncomfortable. Suitable air sensor circuit is which to detect the smells will be presents on this paper. In order to display the output results from the sensor, screen monitor was used. Programmable Interface Controller (PIC) 16F877A was used as the intelligent system that connected between the air sensor circuit and screen monitor which present the output of the room’s conditions. Visual Basic is used to display the three different colors for the output. Red, yellow and green were the chosen colors to indicate danger, warning and safe conditions. Serial port communication is used to interface with PIC16F877A.The hardware and software is implemented in this system modeling and experimental results are presented.